Arbitrary Shaped Homogeneous Invisible Ground Cloak - Mohamad Fazeli; Seyed Hassan Sedighy; Hamid Reza Hassani, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A general approach is introduced to design an arbitrary shaped invisible ground cloak with homogeneous constitutive parameters. The proposed homogenous ground cloak design method facilitates the fabrication process and achieves a variety of choices for choosing the cloak shape. In this approach, an arbitrary polygonal 2D cloak with any number of sides can be designed by dividing the polygonal cloak cross section into triangular segments and applying the proposed method on each one. The full wave simulations results confirm the idea performance, properly. Finally, a homogeneous ground invisible cloak for an object, which its contour is very similar to the lateral cross section of a car is designed and simulated to validate the capability and generality of the proposed idea.